Information Literacy Skills of Research Assistants and Their Educational Needs: Sample of Ankara University - Özel, Nevzat (Information World, 2014)
The continuous development in information and communication technologies has directly affected the environment for acquisition of information and learning as well as reshaping the structure of this environment. Thus the resources, tools, applications and services applied in this environment have also changed and they have been digitally presented. These innovations have made individuals adapt to the new environments in the context of lifelong learning. In other words, it becomes necessary for people to be equipped with “information literacy skills” including “defining the information needs”, “effective access to information”, “assessment of information”, “use of information” and “ transmission and presentation of information” which are indispensable parts of information age. There are significant contributions of educational activities organized by libraries in providing individuals with these skills. In this study, it is aimed to determine library usage of the research assistants at Ankara University, their levels of information literacy skills in the scope of information and communication technologies and identify their educational expectations concerning these issues. This research has been done with 556 participants among 1028 research assistants who have been anticipated to be involved. The descriptive method and a survey as a data collection technique have been used. The results have been analyzed through PASW (Predictive Analytics SoftWare). The results show that the research assistants at Ankara University have difficulty in all stages of research process and they require educational activities on information literacy prepared by libraries.
Keywords: Information literacy; Information literacy education; User education; Libraries